Implementasi Pasal 77 Undang-Undang Lalu Lintas dan Angkutan Jalan Perspektif Sosiologi Hukum : (Studi Kasus di SMAN 1 Ngaglik) - Muhammad Baha Uddin; Agesti Andiriani; Akbar Dwi Saputra; Nurhidayat Aris (Sekolah Tinggi Agama Islam Taruna Surabaya, 2026)
A driver's license (SIM) is an official license from the government in accordance with Article 77 paragraph (1) of Law No. 22 of 2009 on Road Traffic and Transportation, which is granted to the public to be able to drive vehicles on the road according to their type. However, there are requirements regarding when someone can obtain this license, namely the minimum age of 17 (seventeen) years. Nevertheless, Article 77 paragraph (1) is not fully implemented by the public in terms of license ownership as a legality to ride a motorcycle, in this case, by students at SMAN 1 Ngaglik. This issue is the background of this research, namely how the normative (and sollen) provisions regarding this regulation are not automatically applied by the public, or in other words, do not correspond to reality (das sein). This research uses a field research method with an empirical and sociological approach. The data were obtained through interviews, observations, and documentation to identify and describe the factors, causes, and reasons why the 'das sollen' did not meet expectations, thereby resulting in the 'das sein.' The research results show that every student at SMAN Ngaglik has limited resources in the pick-up mechanism, lives far from school, and there is no conventional public transportation. Therefore, there is only one option available, which is to ride their own motorcycle to school, even though according to the rules they are clearly violating them, but due to the environment and social conditions, they act this way.